Imprecision nutrition? Intraindividual variability of glucose responses to duplicate presented meals in adults without diabetes - Hengist, Aaron; Ong, Jude Anthony; McNeel, Katherine; Guo, Juen; Hall, Kevin D (The American journal of clinical nutrition, 2025)
Continuous glucose monitors (CGMs) are used to characterize postprandial glucose responses and provide personalized dietary advice to minimize glucose excursions. The efficacy of such advice depends on reliable glucose responses. To explore within-subject variability of CGM responses to duplicate presented meals in an inpatient setting. CGM data were collected from two inpatient feeding studies in 30 participants without diabetes, capturing 1189 responses to duplicate meals presented ∼1 wk apart from four dietary patterns. One study used two different CGMs (Abbott Freestyle Libre Pro and Dexcom G4 Platinum) whereas the other study used only Dexcom. We calculated the incremental area under the curve (iAUC) for glucose for each 2-h postmeal period and compared within-subject, within-CGM responses to duplicate presented meals using linear correlations, intra-class correlation coefficients (ICC), and Bland–Altman analyses. Individual variability of interstitial glucose responses to duplicate meals were also compared with different meals using standard deviations (SDs). There were weak-to-moderate positive linear correlations between within-subject iAUCs for duplicate meals [Abbott r = 0.46, 95% confidence interval (CI): 0.38, 0.54, P < 0.0001 and Dexcom r = 0.45, 95% CI: 0.39, 0.50, P < 0.0001], with low within-participant reliability indicated by ICC (Abbott 0.28, Dexcom 0.17). Bland–Altman analyses indicated wide limits of agreement (LoA) (Abbott −29.8 to 28.4 mg/dL and Dexcom −29.4 to 32.1 mg/dL) but small bias of mean iAUCs for duplicate meals (Abbott −0.7 mg/dL and Dexcom 1.3 mg/dL). The individual variability of interstitial glucose responses to duplicate meals was similar to that of different meals evaluated each diet week for both Abbott [SDweek1 11.7 mg/dL (compared with duplicate P = 0.01), SDweek2 10.6 mg/dL (P = 0.43), and SDduplicate 10.1 mg/dL] and Dexcom [SDweek1 10.9 mg/dL (P = 0.62), SDweek2 11.0 mg/dL (P = 0.73), and SDduplicate 11.2 mg/dL]. Individual postprandial CGM responses to duplicate meals were highly variable in adults without diabetes. Personalized diet advice on the basis of CGM measurements requires more reliable methods involving aggregated repeated measurements. This trial was registered at clinicaltrials.gov as NCT03407053 and NCT03878108.